ASSESSING THE PERFORMANCE OF CATARACT NET AND OTHER DEEP LEARNING SYSTEMS FOR AUTOMATED CATARACT DETECTION - Shrivastava, Miss Pragya; Gautam, Chandra Shekhar; Kar, Sajal Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The normal lens of the eye, which is located behind the iris and pupil, becomes clouded when a cataract develops. Normally clean, the lens aids in focusing light onto the retina, enabling sharp vision. The formation of a cataract results in an opaque or clouded lens, which distorts or blurs vision. Although aging is frequently linked to cataract development, additional causes include heredity, trauma, certain drugs, or underlying medical disorders like diabetes. The usual symptoms are progressive loss of vision, heightened susceptibility to light, blurred or yellowed colors, and difficulties seeing at night. A thorough eye exam that includes slit-lamp and visual acuity tests is typically used to diagnose cataracts.